PENGARUH TINGKAT PENDIDIKAN, UMK, INVESTASI TERHADAP PENYERAPAN TENAGA KERJA DAN PERTUMBUHAN EKONOMI, KABUPATEN/KOTA DI PROVINSI BALI - Bayu Windayana, Ida Bagus Agung; Darsana, Ida Bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2020)
One of the important benchmarks in determining the success of economic development is economic growth which illustrates a real impact of the development policies implemented. The purpose of this study is to analyze the level of education, MSE, and investment towards employment in the Province of Bali, to analyze the level of education, MSE, investment and labor absorption on economic growth in the Province of Bali, and to analyze the indirect effect of education level, MSE and investment in economic growth through employment in the Province of Bali. This research was conducted in the regencies / cities of Bali Province in 2013-2017. Data collection method used in this study is observation. The data analysis technique used is path analysis. The results of this study indicate the level of education does not have a significant effect on employment in districts / cities of Bali Province, MSEs have a positive and significant effect on employment, investment has a negative and significant effect on employment in districts / cities of Bali Province.